Intentio Spiritus: The Materialist, Pneumatological Origins of Intention in Augustine - Parisi, Alberto (Poligrafi, 2023)
Intention is one of the catchwords of 20th-century Western philosophy. Positively or negatively, it takes a central role in numerous traditions, from phenomenology to analytic philosophy, and in none of them has it anything to do with air or breath. According to its widely accepted lineage, the concept of intention can be traced back to Medieval Scholastic philosophy, specifically to Augustine’s utilisation of this term. It is in Augustine’s intentio animi (the intention of the soul) – most critics argue – that intention first meant directing one’s attention towards something or a voluntary design or plan. In this paper, such a genealogy will not be proved wrong but rather complicated by taking seriously the (anti-)pneumatological context in which Augustine developed his concept of intention and, at the same time, those unheeded studies of his works that claim the origins of his use of intentio to lie in the Ancient Stoic concept of τόνος (tonos, tension or tone). A new study will show that intentio is what allows Augustine every time to prove the spirit to be immaterial, namely to not be a form of material air or breath. By transforming intentio into attentio (attention) first and voluntas (will) later, Augustine makes possible the realm of the immaterial spirit. Furthermore, however, this article also shows that his arguments seem to take for granted and reject an earlier, materialist pneumatological conception of intention, whose traces can be found in some of the works of the Roman Stoic Seneca, as well as in now-lost 4th century CE Christian heretical theories of the Holy Spirit.